Atitude social e inclusão de alunos surdos: os impactos da obrigatoriedade da disciplina de libras nos cursos de formação de educadores - Meira, Fernanda Cilene Moreira de (2012)
The Inclusive Education policy comes up to ensure education for all, that is, regardless of their cultural, economic and physical differences all people have the right to be register and stay in regular school. Thus, students with disabilities and students without disabilities participate together in the educational process. For that teacher education is seen as a key point of attention in this study because their understanding of inclusion and the environment will determine the conditions of learning that population depending on its favorable or unfavorable attitude to inclusion(RANGEL, 1997; OMOTE et al., 2005; PLETSCH, 2009). Thus the concepts of social psychology underlie the analysis of explicit and implicit attitude of students of undergraduate and Education in relation to the inclusion of deaf students, found in the moments before and after passing through a compulsory LSB1 discipline. The research was taken by 38 students graduating in Education, Literature, Mathematics, Physics, Philosophy and Sciences who were enrolled in and frequent in LBS classes. They answered a questionnaire to identify the Likert Scale of Social Attitudes in relation to the inclusion (ELASI ) and the Implicit Association Test (IAT). We carried out the analysis comparing the values of ELASI and TAI in moments before and after the the students take the discipline and confronting explicit measures (them) and implicit (IAT). The comparison between the two stages of ELASI and TAI revealed a significant variation in the explicitly and implicitly attitude of the students when compared the moments before and after they took the LBS discipline. It was revealed a decreased preference for students without disabilities, and most favorably to the inclusion of deaf students. So, based on the finding of significant variation between the measures of the instruments in the moments before and after the passage of discipline, tending to decrease the preference for nondisabled students, it is concluded that the related disciplines including the social attitude has a positive effect on teachers' formation process and presents itself as a public policy effective in minimizing the barriers to inclusion.